The sales agility code : deploy situational fluency to win more sales - Vazzana, Michelle (McGraw Hill, 2023)
"Companies know they need to equip their salespeople to compete in today's market, where buying decisions are more complex, differentiation between suppliers is difficult to discern and so much information is available...decision makers struggle to make sense of what they hear from any potential partner. To the buyer, it all sounds like noise. For these reasons, the decades of research VantagePoint Performance has been conducting on high-performing sales managers and high-performing salespeople is more relevant today than it ever has been. VP recently analyzed the data they've been collecting on over 10,000 sellers and greater than 1,600 sales managers. What became glaringly obvious is that salespeople who could leverage all of their previous methodology trainings to determine the best approach are the ones who accomplish their growth targets. That ability to read the buyer, the situation, needs, and instinctively choose the best approach for each deal and situation is Sales Agility"--